PENGARUH PROMOSI TERHADAP MINAT KONSUMEN ( Studi Evaluasi Strategi Penjualan Jasa Kamar Hotel Asean Pekanbaru) - Risna Debora; Meyzi Herianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aim is to find out how about the promotion (advertising, personal selling, sales promotion and public relations) for achieve the room and to find out the consumer’ interest about (interest transactional, referential interest, interest prehensile and exploratory interest).The population of this research is the consumers of Hotel Asean Pekanbaru. with sampling of 100 people using the formula Slovin. Search procedures performed by accidental sampling of respondents. The research data in the form of primary data, with the questionnaire as a research instrument, data analysis used is by using statistical analysis with SPSS.Based on the results of research by the authors took a conclusion influence of promotion (advertising, personal selling, sales promotion and public relations) against the consumer interest (interest transactional, referential interest, interest prehensile and exploratory interest) on Asean Hotel Pekanbaru of respondents who researched that criteria positions can be categorized agree answer proves that the sale has an influence on consumer interest in the sale room Hotel Asean Pekanbaru, but respondents who answered quite agree is a public relations dimension which is sponsoring, grassroots activities and overcome the problems that are known to the media while in the consumer interest to all dimensions of respondents replied interested.Keywords: promotion (advertising, personal selling, sales promotion and public relations) and the consumer interest (interest transactional, referential interest, interest prehensile and exploratory interest).